Field notes contributed by Stephen J. Dinsmore, summer 1987 - Dinsmore, Stephen J.et al (1987)
Summer report of birds found in central Iowa contributed by Stephen J. Dinsmore. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1987. Epson - sheet feed